2022
DOI: 10.3390/cimb44030079
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Finger E-Box Binding Homeobox 2 as a Prognostic Biomarker in Various Cancers and Its Correlation with Infiltrating Immune Cells in Ovarian Cancer

Abstract: This study investigated the expression of zinc finger E-box binding homeobox 2 (ZEB2), its prognostic significance in various cancers, and the correlation between ZEB2 and infiltrating immune cells and ZEB2-related proteins in ovarian cancer (OV). The Gene Expression Profiling Interactive Analysis tool was used to analyze RNA sequencing data and cancer survival rates, based on normal and tumor tissue data available in The Cancer Genome Atlas (TCGA) database. The Kaplan–Meier plotter and PrognoScan databases we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Based on scientific literature the proteins involved in breast cancer metastasis to lung and published data for their associated transcription factors available in multiple databases was collected to construct an integrated bio-molecular interaction network of Transcription Factor-Target Gene (TFTG). In our study, we used an enlisted 22 metastatic proteins reported through various literatures playing a crucial role in breast cancer lung metastasis [116][117][118][119][120][121][122][123][124][125][126]. The associated transcription factors regulating the expression of these metastatic proteins were fished from the TF2DNA and TF link databases, which offer detailed and extremely reliable information on transcription factor -target gene interactions for numerous organisms, including Homo sapiens.…”
Section: Reconstruction Of Transcription Factor Target Gene (Tftg) Ne...mentioning
confidence: 99%
“…Based on scientific literature the proteins involved in breast cancer metastasis to lung and published data for their associated transcription factors available in multiple databases was collected to construct an integrated bio-molecular interaction network of Transcription Factor-Target Gene (TFTG). In our study, we used an enlisted 22 metastatic proteins reported through various literatures playing a crucial role in breast cancer lung metastasis [116][117][118][119][120][121][122][123][124][125][126]. The associated transcription factors regulating the expression of these metastatic proteins were fished from the TF2DNA and TF link databases, which offer detailed and extremely reliable information on transcription factor -target gene interactions for numerous organisms, including Homo sapiens.…”
Section: Reconstruction Of Transcription Factor Target Gene (Tftg) Ne...mentioning
confidence: 99%
“…The 24 chapters present the contributions of 166 researchers from 16 countries: Brazil (14), China (12), Ecuador (2), Greece (10), Hungary (8), Italy (4), Japan (25), Korea (29), Mexico (11), Poland (5), Portugal (2), Russia (2), Switzerland (7), the UK (1) and the USA (27). The articles reported new molecular findings regarding the following types of cancer: blood [ 1 , 2 ], breast [ 3 , 4 , 5 ], kidney [ 6 ], liver [ 7 , 8 ], lung [ 9 , 10 , 11 , 12 ], ovary [ 10 , 13 , 14 ], prostate [ 15 ], soft tissue [ 16 ], gastric [ 17 , 18 ], testicular [ 19 ], cervical [ 20 , 21 ], and adrenal gland [ 22 ].…”
mentioning
confidence: 99%
“…For several studies, genomic data were downloaded from The Cancer Genome Atlas (TCGA). Liu et al [ 17 ] used these data to determine the prognostic value of miR-942-3p for the gastric cancer, Ferreira et al [ 6 ] to determine the value of GOT2 in clear–cell renal-cell carcinoma, and Kim et al [ 13 ] to determine that of zinc finger E-box binding homeobox 2 in ovarian cancer.…”
mentioning
confidence: 99%